Effect of extrusion screw speed and plasticizer proportions on the rheological, thermal, mechanical, morphological and superficial properties of PLA (2020)
One of the critical processing parameters—the speed of the extrusion process for plasticized poly (lactic acid) (PLA)—was investigated in the presence of acetyl tributyl citrate (ATBC) as plasticizer. The mixtures were obtained by varying the content of plasticizer (ATBC, 10–30% by weight), using a twin screw extruder as a processing medium for which a temperature profile with peak was established that ended at 160 °C, two mixing zones and different screw rotation speeds (60 and 150 rpm). To evaluate the thermo-mechanical properties of the blend and hydrophilicity, the miscibility of the plasticizing and PLA matrix, Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC), oscillatory rheological analysis, Dynamic Mechanical Analysis (DMA), mechanical analysis, as well as the contact angle were tested. The results derived from the oscillatory rheological analysis had a viscous behavior in the PLA samples with the presence of ATBC; the lower process speed promotes the transitions from viscous to elastic as well as higher values of loss modulus, storage modulus and complex viscosity, which means less loss of molecular weight and lower residual energy in the transition from the viscous state to the elastic state. The mechanical and thermal performance was optimized considering a greater capacity in the energy absorption and integration of the components.